2016
DOI: 10.1038/ncomms13354
|View full text |Cite
|
Sign up to set email alerts
|

Structural basis of checkpoint blockade by monoclonal antibodies in cancer immunotherapy

Abstract: Cancer cells express tumour-specific antigens derived via genetic and epigenetic alterations, which may be targeted by T-cell-mediated immune responses. However, cancer cells can avoid immune surveillance by suppressing immunity through activation of specific inhibitory signalling pathways, referred to as immune checkpoints. In recent years, the blockade of checkpoint molecules such as PD-1, PD-L1 and CTLA-4, with monoclonal antibodies has enabled the development of breakthrough therapies in oncology, and four… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
218
0
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 248 publications
(227 citation statements)
references
References 49 publications
4
218
0
5
Order By: Relevance
“…This is consistent with the general observation that the LCDR2 of antibodies is often not involved in antigen binding. The previously reported structures of PD-L1 in complex with BMS-963559 or avelumab demonstrated that these two antibodies similary involved only five of the six CDRs in the interaction with PD-L1, leaving LCDR2 without any binding to PD-L1 38, 39 .
Figure 1Crystal structures of PD-1 in complex with atezolizumab and durvalumab. ( a ) Ribbon representation of the complex structure of PD-L1/atezolizumab Fab fragment.
…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…This is consistent with the general observation that the LCDR2 of antibodies is often not involved in antigen binding. The previously reported structures of PD-L1 in complex with BMS-963559 or avelumab demonstrated that these two antibodies similary involved only five of the six CDRs in the interaction with PD-L1, leaving LCDR2 without any binding to PD-L1 38, 39 .
Figure 1Crystal structures of PD-1 in complex with atezolizumab and durvalumab. ( a ) Ribbon representation of the complex structure of PD-L1/atezolizumab Fab fragment.
…”
Section: Resultsmentioning
confidence: 95%
“…Recently, the crystal structures of PD-L1 in complex with the Fab fragment of BMS-936559 and the single-chain Fv fragment (scFv) of avelumab have been determined, revealing details of the antigen-antibody interactions 38, 39 . However, the epitopes and the PD-L1 blocking mechanism of atezolizumab and durvalumab remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…[18] The binding surfaces of peptides -57 and -71 within PD-L1 overlap partially with the epitopes of anti-PD-L1 antibodies (atezolizumab, avelumab, durvalumab, and BMS-936559 (Supporting Information, Figure S15)). [19,20] Analysis of the interactions of the residues of the antibodies avelumab and BMS-936559 and the peptides shows that several residues of the peptides and the antibodies interact similarly. A number of the residues of peptide-71 mimic the amino acids of the VH domain of avelumab responsible for the interactions with PD-L1 (Supporting Information, Figures S16 and S17): for example, the hydrophobic side chains of peptide-71: 71 Phe1, 71 NMeNle3 and 71 NMePhe7, interact similarly to A Ile33, A Pro53 and A Ile57, respectively (subscript A indicates the avelumab residues).…”
mentioning
confidence: 99%
“…Moreover, a comparison of the crystal structure of the PD-1/nivolumab Fab complex (PDB ID: 5GGR) with that of PD-1/pembrolizumab (PDB ID: 5GGS) [29] indicated that the epitopes of both antibodies directly occupy part of the PD-L1 binding site and can thus outcompete PD-L1 for binding to PD-1.…”
Section: Cocrystal Structures With Monoclonal Antibodiesmentioning
confidence: 99%